The Role of Religious Leaders in Promoting Religious Moderation in Society - Neneng Khuliah; Siti Ropiah; Siti Salamah; Nanang Kosim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the role of religious leaders in promoting religious moderation among communities, particularly in the context of a pluralistic and diverse social life. Religious moderation is a religious approach that emphasizes tolerance, fairness, balance, and the avoidance of extreme attitudes in practicing religion. Religious leaders hold a strategic position as role models and communicators of religious values who can influence the attitudes and behaviors of the community. The method used in this study is a descriptive qualitative method, with data collection techniques including in-depth interviews with religious leaders from various faiths (Islam, Christianity, Hinduism, and Buddhism), participatory observation of religious and social activities, and documentation studies from literature and policies related to religious moderation. The research location is focused on areas with a high degree of religious diversity, allowing for the direct exploration of moderation practices. The results of the study indicate that religious leaders play a significant role in conveying messages of moderation through sermons, lectures, interfaith dialogues, and religious social activities. The main findings show that religious leaders who are active in interfaith forums and tolerance- strengthening programs tend to be more effective in instilling the values of moderation in their congregations. On the other hand, there are still challenges such as the lack of training, the influence of identity politics, and resistance from conservative groups that hinder the optimal role of religious leaders. The conclusion of this study is that religious leaders are key actors in grounding religious moderation within a diverse society. They can serve as agents of change who bridge differences and prevent conflicts based on religion. The implementation of this research's findings can be carried out through strengthening the capacity of religious leaders in terms of religious moderation literacy, government policy support in mainstreaming tolerant preaching, and collaboration among religious and educational institutions to create constructive dialogue spaces.